Ocena transportu rumowiska zawieszonego z wykorzystaniem nefelometrycznych i tradycyjnych pomiarów mętności wody na przykładzie kaskady dolnej Brdy = The estimation of suspended sediment transport using nefelometric and traditional measurements of turbidity of water on an example of the cascade lower Brda River - Szatten, Dawid Aleksander (Journal of Education, Health and Sport, 2016)
Szatten Dawid. Ocena transportu rumowiska zawieszonego z wykorzystaniem nefelometrycznych i tradycyjnych pomiarów mętności wody na przykładzie kaskady dolnej Brdy = The estimation of suspended sediment transport using nefelometric and traditional measurements of turbidity of water on an example of the cascade lower Brda River. Journal of Education, Health and Sport. 2016;6(1):64-72. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44629 http://ojs.ukw.edu.pl/index.php/johs/article/view/44629 http://pbn.nauka.gov.pl/works/692137 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.12.2015. Revised 25.12.2015. Accepted: 09.01.2016. Ocena transportu rumowiska zawieszonego z wykorzystaniem nefelometrycznych i tradycyjnych pomiarów mętności wody na przykładzie kaskady dolnej Brdy The estimation of suspended sediment transport using nefelometric and traditional measurements of turbidity of water on an example of the cascade lower Brda River Dawid Szatten Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Instytut Geografii, 85-428 Bydgoszcz, ul. Mińska 15 Streszczenie Ocenę transportu rumowiska zawieszonego, dla zbiorników retencyjnych kaskady dolnej Brdy, przeprowadzono w celu porównania metod: tradycyjnej (wagowej) oraz nefelometrycznej (optycznej). Analizy dokonano na podstawie badań terenowych przeprowadzonych poniżej Zbiornika Smukała w latach 2014 - 2015. Obejmowały one pobór prób w celu oznaczenia wartości wskaźnika zawiesina ogólna (metoda tradycyjna) oraz nefelometrycznej mętności wód (metoda laserowa). Pobór połączony był z obserwacjami stanów wody, umożliwiając określenie sytuacji hydrologicznej. Zebrane dane zinterpretowano za pomocą podstawowych metod statystycznych. Stwierdzono, iż rzeka Brda charakteryzuje się niewielkim obciążeniem w materiał zawieszony. Obserwacje zmącenia wód, umożliwiły określenie chwilowej dynamiki zawiesin oraz wskazanie głównego źródła pochodzenia analizowanej składowej transportu fluwialnego. Otrzymane dane wskazują na możliwość zamiennego stosowania porównywanych w artykule metod. Abstract The evaluation of the suspended sediment transport was conducted on artificial reservoir of cascade of lower Brda River, to compare methods: traditional (weight) and nephelometric (optical). The analysis was based on field research conducted below the Smukała Reservoir in the years 2014 - 2015. These included sample collection for determining the value of total suspension (traditional method) and nephelometric turbidity of water (laser method). Sampling was connected with the observations of water levels, for specifying the hydrological situation. The collected data were interpreted using basic statistical methods. Was found that the the Brda River is characterized by a low suspended sediments load. Observations turbidity of water was possible to determine temporary dynamics of suspended sediments and indicate the main source of the suspended material. Received in article data indicate that the compare methods are interchangeability. Słowa kluczowe: transport rumowiska zawieszonego, mętność wód, zawiesina ogólna, nefelometryczne pomiary mętności, sztuczne zbiorniki wodne. Key words: suspended sediment transport, turbidity of water, total suspension, nefelometric measurements, artificial reservoir.